Case Report: Unedited allogeneic chimeric antigen receptor T cell bridging to conditioning-free hematopoietic stem cell transplantation for a child with refractory Burkitt lymphoma - Yang, Xiaomin; Luo, Chengjuan; Qian, Juan; Huang, Xiaohang; Zhang, Jian; Wang, Jianmin; Luo, Changying; Qin, Xia; Li, Benshang; Chen, Jing (Frontiers in Immunology, 2023)
Purpose Burkitt lymphoma (BL) is the most common tumor of non-Hodgkin’s lymphoma (NHL) in children, accounting for about 40% of cases. Although different combined short-course chemotherapies have achieved a good effect, refractory/relapsed BL has a poor prognosis with cure rates less than 30%. Chimeric antigen receptor T cell (CAR-T) therapy has developed rapidly in recent years and achieved excellent results in acute lymphoblastic leukemia (ALL). However, in some cases, there is a failure to produce autologous CAR-T cells because of T-cell dysfunction. In such cases, allogeneic CAR-T therapy has to be considered. Methods A 17-year-old boy with stage II BL did not respond to extensive chemotherapy and sequential autologous CAR-T therapy. Lentiviral vectors containing anti-CD20-BB-ζ (20CAR) and anti-CD22-BB-ζ (22CAR) transgenes were used to modify the T cells from an HLA-identical matched unrelated donor. Flow cytometry was used to assess the cytokine analyses and CAR-T cell persistence in peripheral blood, enumerated by qPCR as copies per ug DNA. Informed consent for autologous/allogeneic CAR-T therapy was obtained from the patient and his legal guardian. Results Unedited HLA-matched allogeneic CD20 and CD22 CAR-T cells were infused after lymphodepletion chemotherapy with cyclophosphamide and fludarabine. The patient experienced Grade IV cytokine release syndrome (CRS) and went into complete remission (CR) after anti-inflammatory treatment including tocilizumab. Because of persistent pancytopenia and full donor chimerism, the same donor’s conditioning-free peripheral blood stem cells were successfully transplanted 55 days post CAR-T. Neutrophils were engrafted at day +11 and platelets were rebuilt at day +47 without obvious acute graft-versus-host disease (GVHD), but there was mild chronic GVHD in the skin and eyes. Currently, active anti-rejection therapy is still underway. Conclusion Unedited HLA-matched allogeneic CAR-T cell therapy could be an innovative, effective, and safe treatment for children with refractory/relapse BL without obvious acute GVHD. Conditioning-free allogeneic hematopoietic stem cell transplantation (HSCT) from the same donor is feasible for a patient with full donor T-cell chimerism after allogeneic CAR-T. It cannot be ignored that close GVHD monitoring is needed post HSCT.